Methodological Approaches to Estimation of Energy Efficiency within the Framework of the Concept of Green Economy and Sustainable Development - Matraeva, Liliia V.; Goryunova, Natalia A.; Smirova, Svetlana N.; Babenko, Maria I.; Erokhin, Sergey G.; Solodukha, Peter V. (International Journal of Energy Economics and Policy, 2017)
The transition of the world developed countries to a "low-carbon" economy and "green" economic growth leads to the fact that energy indicators are actively included in the system of environmental and economic assessments at the present stage of development. Taking into account the synergetic approach required in the analysis of energy efficiency, reflecting its impact on three main areas of activity: economic, social and environmental, we consider the index of adjusted net savings to be the final link of the World Bank’s "green" indicators. Based on the analysis, it is argued that there are fundamental differences in economic policy regarding energy efficiency for different groups of countries. The experience of leading foreign countries in the field of energy efficiency is summarized, such as Germany and Japan, which occupy leading positions in the energy efficiency rating. However, the authors pay special attention to two more countries: Finland and China. Keywords: green economy, green growth, energy saving, green accounts, energy efficiency, low-carbon economy JEL Classification: Q4